"Caribou was the reason, and everything else happened after": Exploring Inuit-caribou relationships through community-based documentary film in Labrador, Canada. - Borish, David (Global Environmental Change, 2021)
Across the Circumpolar North, the decline of caribou populations pose a range of complex challenges for communities that have depended, and continue to depend, on caribou for many aspects of their health and wellbeing. In Labrador, Canada, caribou herds have recently experienced rapid population declines, including a 99% decline of the George River herd, resulting in a total hunting ban placed on that herd in 2013. Despite this decline, little is known about the ways in which these population changes are affecting Inuit wellbeing across Labrador. As part of an Inuit-led multiyear, multimedia project called HERD: Inuit Voices on Caribou, this dissertation research worked in partnership with Inuit from the Nunatsiavut and NunatuKavut regions of Labrador, Canada, to document, explore, and communicate Inuit knowledge and lived experiences about their relationship with caribou. The central goal was to characterize how changing caribou populations impact the health and wellbeing of Inuit through the advancement and co-production of community-based documentary film work. Data were collected through 84 in-depth, filmed interviews (Nunatsiavut region: n=54; NunatuKavut region: n=30) conducted between January-April 2019. The data were then analyzed using a video-based qualitative analysis, constant-comparative methods, and inductive qualitative approach. This research was informed by decolonizing and community-based participatory research methodologies. Results indicated that caribou are foundational for various elements of Inuit wellbeing, including culture, food security, social connections, and emotional wellbeing. The changes in caribou populations are resulting in losses to cultural knowledge; alterations to Inuit identity; influences on family, community, and regional social connections; and feelings of anxiety, sadness, and uncertainty about the future of caribou-Inuit relationships. In parallel with these findings, this dissertation also outlines the advancements made in using documentary film as a methodological ...